Revolutionary Morality: The (Anti)Religion Confessed by Maximilien Robespierre during the French Revolution - Ulišauskas, Ignas (Vilnius University Open Series, 2025)
The aim of this paper is to gain insight into Maximilien Robespierre’s (1758–1794) religious consciousness. He, like his fellow and enemy revolutionaries, lived in a world where it was more understandable to be religious than to not to be. With the outbreak of the French Revolution, it can be seen that Robespierre used religious or religiously subtextual signs in his rhetoric. While scholars have noted that Robespierre established the Cult of Supreme Being, it is evident that his faith was prominently more multifaceted and nuanced. An analysis of his rhetoric reveals the presence of an authentic personal faith, which he leveraged to combat his political enemies, justify revolutionary violence, and advance the goals of the French Revolution.
Keywords: Maximilien Robespierre; religious consciousness; French Revolution; fanaticism; atheism; dechristianization; Supreme Being; terror